HYPERFINE INTERACTIONS, INCLUDING BHF[FRFE], STUDIED IN THE DECAY CHAIN OF RA-225 BY ALPHA-ANISOTROPY AND GAMMA-ANISOTROPY MEASUREMENTS - Lindroos, M; Richards, P; Rikovska, J; Stone, N; Oliveira, I; Nishimura, K; Booth, M (Kluwer Academic Publishers, 1992)
A low temperature nuclear orientation experiment has been performed on the 14.8d225Ra activity. Gamma anistotropy [221Fr (4.8m) and213Bi (45.6m)] and alpha anisotropy [225Ac (10.0d),221Fr,217At (32.3ms) and209Po (4.2μs)] measurements has been carried out and values for the hyperfine field of225Ac and221Fr in iron and the magnetic moment of213Bi are reported. © 1992 J.C. Baltzer A.G., Scientific Publishing Company.